ANALISIS KEMAMPUAN LITERASI SAINS SISWA SMP NEGERI 2 BATAHAN PADA PEMBELAJARAN FISIKA MATERI PESAWAT SEDERHANA DITINJAU DARI ASPEK KONTEKS, KONTEN, DAN PROSES SAINS - Faisal; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to describe and analyze the profile of scientific literacy skills of VIII grade students at SMP Negeri 2 Batahan in physics learning on simple machines material reviewed from context, content, and science process aspects. This descriptive quantitative research used a sample of 32 students from class VIII-A selected through cluster sampling. The data collection instrument was a scientific literacy test consisting of 8 multiple choice questions and 4 essay questions based on the PISA 2015 framework. The results showed that students' overall scientific literacy ability was at a moderate category with an average percentage of 56.38%. Based on per-aspect analysis, the context aspect obtained the highest percentage of 64.06% (moderate category), followed by the content aspect at 60.11% (moderate category), and the science process aspect at 47.56% (low category). The low science process ability reflects the lack of inquiry and practicum activities in physics learning. This study concludes that there is an imbalance in students' scientific literacy development with the pattern: Context > Content > Science Process, so a reorientation of physics learning towards more comprehensive development of students' scientific skills is needed.